2016
DOI: 10.1088/1752-7155/10/1/016010
|View full text |Cite
|
Sign up to set email alerts
|

Expanding metabolite coverage of real-time breath analysis by coupling a universal secondary electrospray ionization source and high resolution mass spectrometry—a pilot study on tobacco smokers

Abstract: Online breath analysis is an attractive approach to track exhaled compounds without sample preparation. Current commercially available real-time breath analysis platforms require the purchase of a full mass spectrometer. Here we present an ion source compatible with virtually any preexisting atmospheric pressure ionization mass spectrometer that allows real-time analysis of breath. We illustrate the capabilities of such technological development by upgrading an orbitrap mass spectrometer. As a result, we detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 57 publications
1
61
0
Order By: Relevance
“…In studies on human breath, more than 3000 different VOCs and particles have been detected, where most of the VOCs are at low concentrations, i.e., from ppm to ppb or ppt [81][82][83][84][85][86]. A healthy adult human has a respiratory rate of 12−15 breaths/min at rest, inspiring and expiring 6-8 L of air per minute.…”
Section: Human Breath Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies on human breath, more than 3000 different VOCs and particles have been detected, where most of the VOCs are at low concentrations, i.e., from ppm to ppb or ppt [81][82][83][84][85][86]. A healthy adult human has a respiratory rate of 12−15 breaths/min at rest, inspiring and expiring 6-8 L of air per minute.…”
Section: Human Breath Biomarkersmentioning
confidence: 99%
“…The most predominant endogenous compounds in breath are isoprene (12-580 ppb), ethanol (13-1000 ppb), methanol (160-2000 ppb), and acetone (1.2-1800 ppb); other alcohols are present in the very low concentration. Only a small number of VOCs are common to everyone (isoprene, acetone, ethane, and methanol) which are products of metabolic processes and some of these VOCs (ethane, n-pentane, butane, ethanol, acetone) have been identified as breath biomarkers [81][82][83][84][85][86].…”
Section: Human Breath Biomarkersmentioning
confidence: 99%
“…In personalized healthcare, breath analysis has been demonstrated by clinicians to allow determination of the smoking habits of an individual [107][108][109][110]. Currently, blood and urine analysis of cotinine (a primary metabolic product of nicotine) was used as a diagnostic tool.…”
Section: Personalized Nutrition and Healthcarementioning
confidence: 99%
“…An improved LC-MS method that simplified the extraction and clean-up steps in a simple online column-switching HPLC setup demonstrated identification of 7 prostanoids directly from hepatocytes in a 96 well format [11*]. Similarly, a pilot study demonstrated the possibility of identifying degraded products of oxidized free fatty acids directly from exhaled breath in smokers in a high throughput manner [12*]. …”
Section: Oxidative Lipidomicsmentioning
confidence: 99%